One-year post-acute COVID-19 syndrome and mortality in South Korea: a nationwide matched cohort study using claims data - Won, Jung-Hyun; Hong, Yesol; Kim, Siun; Lee, Howard (Frontiers in Public Health, 2024)
Background Current understanding of post-COVID-19 syndrome in South Korea is primarily based on survey studies or research targeting specific patient groups, such as those hospitalized. Moreover, the majority of relevant studies have been conducted in European and North American populations, which may limit their applicability to the South Korean context. To address this gap, our study explores the one-year outcomes of COVID-19, focusing on the potential post-acute syndrome and all-cause mortality in South Korea. Methods This retrospective cohort study used nationwide claims data in South Korea, including adults aged >18 with records between January 20, 2020, and February 25, 2021. Patients were classified into COVID-19 and non-COVID-19 groups and matched 1:1 based on propensity scores. Primary outcomes were 12-month post-acute COVID-19 syndrome and all-cause mortality. Results The study involved 34,802 matched patients. The COVID-19 group had significantly elevated risks of coagulopathies (OR = 2.70 [2.24, 3.28]; p < 0.001), chronic lower respiratory diseases (OR = 1.96 [1.80, 2.14]; p < 0.001), symptoms of the circulatory and respiratory systems (OR = 1.91 [1.80, 2.04]; p < 0.001), mood disorders (OR = 1.67 [1.51, 1.86]; p < 0.001), cardiac diseases (OR = 1.39 [1.21, 1.59]; p < 0.001), and symptoms of cognition, perception, emotional state, and behavior (OR = 1.15 [1.04, 1.27]; p = 0.005). All-cause mortality was higher in the COVID-19 group during the 6 months (OR = 1.34 [1.06, 1.69]; p = 0.015), but gradually decreased, reaching an OR of 0.996 ([0.83, 1.19]; p = 0.964) at 1 year. Conclusion In South Korea, the 12-month post-acute COVID-19 syndrome includes coagulopathies, respiratory issues, mood disorders, and cardiac diseases. The risk of all-cause mortality post-COVID-19 is heightened for up to 6 months, then significantly decreases and resolves within a year.